Note—Can a Reduction in Set Up Costs Indeed Increase Total Costs? - Gerchak, Yigal (Management Science, 1988)
Zangwill (Zangwill, W. I. 1987. From EOQ towards ZI. Management Sci. 33 1209–1223.) has constructed an example which purports to show that reducing set up costs can increase total cost. We show that this happened as a result of restricting the policies to be of a “greedy” nature. The expected cost of truly optimal policies is shown not to increase.